The Role of Cooperation with Allobank in Increasing Sales of Outbound Tour Packages at Antavaya Bali (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
This study aims to determine the role of cooperation with Allobank in increasing sales of outbound tour packages at Antavaya Bali. The population in the study were 200 customers who had purchased outbound tour packages at Antavaya Bali and used Allobank services. Data analysis techniques used validity test, reliability tests, classical assumption test, multiple linear regression analyses, coefficient of determination test, and t-test. From the results of the study, the results obtained were that cooperation with Allobank had a positive and significant effect on the level of sales, where the t value was 14.482 and the sig value was 0.000. The magnitude of the influence of cooperation with Allobank on the level of sales of outbound tour packages is 51.4%